REPRODUCTIVE HEALTH RIGHTS OF WOMEN WORKERS: CHALLENGES AND SOLUTIONS IN MENSTRUAL LEAVE IMPLEMENTATION IN INDONESIA - Idianto; Saraswati, Retno; Cahyaningtyas, Irma (Veredas do Direito, 2026)
The implementation of menstrual leave for female workers represents a significant component of the protection of reproductive rights, as outlined in Indonesia’s Labour and Health Laws. Law No. 13 of 2003 provides female workers with the entitlement to refrain from work on the first and second days of their menstrual period, ensuring that they continue to receive their wages during this time. Nonetheless, implementing this is frequently obstructed by insufficient understanding among companies and prevailing negative perceptions of women who assert this right. Conversely, Law Number 17 of 2023 regarding Health establishes a legal framework to safeguard women’s reproductive health, including the provision of quality health services. For the effective implementation of menstrual leave rights, it is essential to foster collaboration among the government, employers, and relevant agencies. This can be achieved through socialisation and education that promote equality and welfare for female workers in Indonesia.